Strategi Diskominfo dalam Pemerataan Jaringan Internet di Kabupaten Parigi Moutong Provinsi Sulawesi Tengah - Juanda Juanda; Andi Izzulhaq (Institut Pemerintahan Dalam Negeri (IPDN) Kampus Sumatera Barat, 2023)
Based on data from the Diskominfo of Parigi Moutong Regency, there are still 94 villages with blank spots out of 278 villages. It shows that there are still many areas that need better internet access. This study aims to analyze the condition of the internet network in Parigi Moutong Regency. It will formulate a strategy for equitable distribution of the internet network in Parigi Moutong Regency. The data analysis technique in this study uses descriptive and SWOT analysis methods. A SWOT analysis determines the strengths or weaknesses and opportunities and threats from Diskominfo in distributing the internet network. The result of this research is that there are obstacles and hazards in distributing the Internet network. Here are some alternative strategies: synergizing with the community, private sector, and the central government in building telecommunications facilities, improving the employee recruitment system, and maximizing the budget and infrastructure for equitable distribution of the internet network.